Pengembangan Media Pembelajaran Komik Berbasis Qr Code pada Mata Pelajaran PPKn Kelas III SD - Faizal Tri Haryanto; Leo Charli; Armi Yuneti (Journal of Elementary School (JOES), 2023)
This study aims to develop a comic learning media design based on Qr Code. Testing the validity and practicality of Qr Code based comic media in Class III PPKn lessons at SD N 1 Marga Sakti. This type of research is Research and Development with a 4-D (Four-D) development model. The subjects of this study were media experts, linguist, material expert, teachers, third grade students at SD N 1 Marga Sakti. Data collection techniques using interviews and questionnaires. Based on the results of the validity assessment conducted by the three experts, namely media experts who scored 0.76 with the classification "Quite high", linguists who scored 0.85 with the classification "High", and material experts who scored 0.84 with the classification “Tall”. These results shows that the Or Code-based comic learning media meets the valid criteria with an average score of 0.83. Meanwhile, the results of the analysis of the practicality assessment sheet for teachers and students show that the Qr Code-based comic learning media meets the practical criteria with an average score of 92%. Based on the results from the validity and practicality trials, it can be concluded that Qr Code-based comic media meets the validity and practical criteria and can be used in learning activities Keywords: PPKn, Qr Code, Learning Media, Development, Comics